Increased serum IL-1 level and activated JAK2/STAT3 signaling pathway of cancer tissue in patients with gastric cancer - NIU Shi-wei, SU Yun, GONG Hong-xia, LI Ting-ting, ZENG Yuan-ding, ZHANG Han, NIE Peng (Jichu yixue yu linchuang, 2022)
Objective To explore the role of elevated serum interleukin 1(IL-1) levels in patients with gastric cancer and activation of JAK2/STAT3 signaling pathway in tissues of gastric cancer. Methods A total of 30 gastric cancer surgery patients and 30 healthy subjects were selected from Wuwei Cancer Hospital of Gansu Province; The levels of IL-1 and IL-10 in serum was determined by enzyme-linked immunosorbent assay (ELISA); Immunohistochemistry and Western blot were used to detect the contents of Bcl-2, Bax and JAK2,STAT3, pJAK2, pSTAT3, Bcl-2, Bax in tissues. The contents of JAK2, STAT3, Bcl-2 and Bax genes were measured by RT-qPCR. Results Compared with the control group, the level of IL-1 in the serum of patients with gastric cancer was up-regulated, and the level of IL-10 was down-regulated(P＜0.05); The content of Bcl-2 in cancer tissue was significantly higher than that in the normal group and the adjacent group, but the Bax content showed an opposite profile(P＜0.05). Compared with the control group, JAK2, STAT3, pJAK2, pSTAT3 and Bcl-2 protein content in cancer tissue and adjacent tissues were increased, while the content of Bax was decreased(P＜0.05). Compared with the adjacent tissues, the JAK2, STAT3, pJAK2, pSTAT3 and Bcl-2 protein contents in cancer tissues increased, while the Bax content was decreased(P＜0.05). Compared with the control group, the contents of JAK2, STAT3 and Bcl-2 mRNA in cancer tissues and adjacent tissues were increased, while Bax mRNA was decreased(P＜0.05). Compared with adjacent tissues, the contents of JAK2, STAT3 and Bcl-2 mRNA in cancer tissues increased, while the content of Bax mRNA was decreased(P＜0.05). Conclusions Abnormal elevation of proinflammatory factors and abnormal activation of JAK2/STAT3 signaling pathway are closely related to the occurrence and development of gastric cancer.